(POST-)DIGITAL TRANSFORMATION OF RUPTURE: THE CZECH MEDIA LANDSCAPE AND ITS THREATS - Šimková, Karolina; Wimmer, Jeffrey (AoIR Selected Papers of Internet Research, 2026)
This study is grounded in a discursive-material framework, which enables us to pay attention to the material as well as the discursive dimensions of the current rupture in democracy and media. Empirically it focuses on threats to the media landscape from the perspectives of regulatory institutions, news media organizations, and citizens. To this end, twelve interviews with editors-in-chief and journalists from leading news media outlets (print, TV, radio, online, and community media) and four interviews with representatives of major national media authorities were conducted in the spring and summer of 2024. Additionally, four focus group discussions with citizens (n=38) from heterogeneous socio-demographic backgrounds were carried out. We identify five threats to news media and their possible implications for democracy from the perspective of citizens. These threats all have their discursive and material components. Conversely, journalists identify additional threats, which they describe as manifestations of an ongoing crisis: the business-model fragility, media ownership concentration in the hands of a small group of investors, and populist attacks on public-service media. Media authorities also point to the material resources of the media landscape, with a discussion about the role of technology and the organizational infrastructures that support them. Building on our findings, we argue that the material and discursive implications of datafication – exemplified by the biggest Czech platform Seznam.cz and AI-driven workflows, not only intensify these two processes but have become crucial for understanding the rupture between media and democracy.